Multimodal quantitative MRI atlas of the human brain in healthy young adults: clinical investigative study - Pfirrmann, Julia; Adlung, Anne; Hermann, Ingo; Weber, Claudia Ellen; Ebert, Anne; Zöllner, Frank G.; Gass, Achim; Eisele, Philipp (Journal of neuroimaging, 2025)
Background and Purpose Quantitative MRI provides insights into (patho-) physiological processes of the brain macro- and microstructure. In this study, we applied a multimodal MRI approach to determine quantitative values of the brain in healthy young adults. Methods 3 T MRI including sodium MRI (4.0 mm nominal isotropic resolution), 3D T1-weighted magnetization-prepared rapid acquisition gradient-echo (spatial resolution = 0.9 mm × 0.9 mm × 0.9 mm), T2-fluid attenuated inversion recovery (spatial resolution = 0.4 mm × 0.4 mm × 5.0 mm), diffusion-weighted imaging (spatial resolution = 1.0 mm × 1.0 mm × 4.0 mm), PD/T2 (spatial resolution = 1.0 mm × 1.0 mm × 2.0 mm), and MR fingerprinting including T1 and T2* relaxation times (spatial resolution = 1 mm × 1 mm × 2 mm) was performed on 40 healthy young adults (28 women, mean age: 24.55 years). Results Mean values for the gray matter were as follows—apparent diffusion coefficient (ADC): 0.95 ± 0.03 × 10−3 mm2/s, total sodium concentration (TSC): 41.99 ± 2.35 mM, T1: 1338.04 ± 46.29 ms, T2*: 63.39 ± 2.94 ms. For the white matter, mean values were as follows—ADC: 0.79 ± 0.02 × 10−3 mm2/s, TSC: 36.08 ± 5.62 mM, T1: 968.47 ± 48.35 ms, T2*: 53.62 ± 8.06 ms, and for the deep gray matter, mean values were as follows—ADC: 0.85 ± 0.04 × 10−3 mm2/s, TSC: 38.23 ± 2.91 mM, T1: 1087.24 ± 39.77 ms, T2*: 54.53 ± 7.15. Conclusion Our multimodal, quantitative MRI atlas of the human brain in healthy young adults provides meaningful in vivo insights into the brain microstructure and can be used for reference in future studies.
Erstmals veröffentlicht: 25. Juli 2025
Gesehen am 11.11.2025